2006
DOI: 10.1016/j.visres.2005.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Detection of colour changes in a moving object

Abstract: The colour-changing stimulus paradigm is based on a tacit assumption that kinematic attributes (velocity, movement direction) do not affect the detection of colour change (). In this study three experiments are reported that clearly demonstrate that the time needed to detect changes in colouration of a moving stimulus becomes shorter with its velocity. The reduction of reaction time with increase of velocity is a purely kinematic effect independent on the reduction of reaction time caused by the stimulus uncer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
19
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 43 publications
5
19
0
Order By: Relevance
“…This finding is consistent with Viviani and Aymoz (2001). In a previous article, reaction times to fast-moving objects were found to be reduced (Kreegipuu et al, 2006). It may be that reaction times are differentially affected by stimulus velocity, whereas relative judgments are not.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This finding is consistent with Viviani and Aymoz (2001). In a previous article, reaction times to fast-moving objects were found to be reduced (Kreegipuu et al, 2006). It may be that reaction times are differentially affected by stimulus velocity, whereas relative judgments are not.…”
Section: Discussionsupporting
confidence: 88%
“…Experiment 2 was similar to Experiment 1, except that we varied the velocity of object motion. It was possible that the detection of color changes would be shortened at high velocities (Kreegipuu, Murd, & Allik, 2006).…”
Section: Abrupt Versus Continuous Changesmentioning
confidence: 99%
“…The experimental setup (see figure 1) was similar to that of our previous study (Kreegipuu et al 2006), except that the task was to compare the simultaneity of two events (a colour change in a moving object and a short auditory signal). 2.1.1 Participants.…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that reaction time (RT) increases with stimulus uncertainty (Mattes et al 2002;Na« a« ta« nen 1972) and it would be expected that the change in colour is detected faster when the uncertainty of the change is smaller. Indeed, our previous research (Kreegipuu et al 2006) has shown that RTs decrease with an increase in colour-change probability. However, this decrease was independent of the effect of velocity: it still took less time to detect colour change in a fast-moving stimulus than in a slow-moving or stationary stimulus, irrespective of the probability of the change (Kreegipuu et al 2006; see also Monnier and Shevell 2004).…”
mentioning
confidence: 88%
See 1 more Smart Citation